Ln(x)+ln(6)=2

Simple and best practice solution for Ln(x)+ln(6)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Ln(x)+ln(6)=2 equation:


Simplifying
Ln(x) + ln(6) = 2

Multiply nL * x
nxL + ln(6) = 2

Reorder the terms for easier multiplication:
nxL + 6ln = 2

Reorder the terms:
6ln + nxL = 2

Solving
6ln + nxL = 2

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-1nxL' to each side of the equation.
6ln + nxL + -1nxL = 2 + -1nxL

Combine like terms: nxL + -1nxL = 0
6ln + 0 = 2 + -1nxL
6ln = 2 + -1nxL

Divide each side by '6n'.
l = 0.3333333333n-1 + -0.1666666667xL

Simplifying
l = 0.3333333333n-1 + -0.1666666667xL

See similar equations:

| 6=8s-3/4-20 | | -1+a/5=-4 | | 6x^2-2x+4=24 | | 8m+3=5m+18 | | x+(x*0.0975)=25 | | x^2-7x+4=-6 | | (-50)x(-4)= | | 5x^2+7x-16=32-27x | | (-8)x(-2)= | | 1200=3x+y | | 25x+70= | | 4=6(x-5)+2-5x | | -0.25+0.75= | | 1/3x+7/6x=220 | | x+9=5(2x-4) | | 5v+7=-23 | | 2k^2-14k-30=k^2+3k+30 | | 22x+100= | | -4(x-1)=-1-4x | | 9x^2=6x | | -13x(-4)= | | x^2+5X-510=0 | | M-5/2=-9 | | 20x+5x-20=21x | | 1/11*11 | | 20=11-p | | 19-6b=3+2b | | -2.6=-1.274 | | x-0.3=4.5 | | 14/3x3x12/7 | | 6x(-1)= | | y=7/4-3 |

Equations solver categories